Exploring the Saturn system in the thermal infrared: The Composite Infrared Spectrometer - Flasar, F; Kunde, V; Abbas, M; Achterberg, R; Ade, P; Barucci, A; Bezard, B; Bjoraker, G; Brasunas, J; Calcutt, S; Carlson, R; Esarsky, C; et al. (2004)
The Composite Infrared Spectrometer (CIRS) is a remote-sensing Fourier Transform Spectrometer (FTS) on the Cassini orbiter that measures thermal radiation over two decades in wavenumber, from 10 to 1400 cm- 1 (1 mm to 7μ m), with a spectral resolution that can be set from 0.5 to 15.5 cm- 1. The far infrared portion of the spectrum (10-600 cm - 1) is measured with a polarizing interferometer having thermopile detectors with a common 4-mrad field of view (FOV). The middle infrared portion is measured with a traditional Michelson interferometer having two focal planes (600-1100 cm- 1, 1100-1400 cm- 1). Each focal plane is composed of a 1× 10 array of HgCdTe detectors, each detector having a 0.3-mrad FOV. CIRS observations will provide three-dimensional maps of temperature, gas composition, and aerosols/condensates of the atmospheres of Titan and Saturn with good vertical and horizontal resolution, from deep in their tropospheres to high in their mesospheres. CIRS's ability to observe atmospheres in the limb-viewing mode (in addition to nadir) offers the opportunity to provide accurate and highly resolved vertical profiles of these atmospheric variables. The ability to observe with high-spectral resolution should facilitate the identification of new constituents. CIRS will also map the thermal and compositional properties of the surfaces of Saturn's icy satellites. It will similarly map Saturn's rings, characterizing their dynamical and spatial structure and constraining theories of their formation and evolution. The combination of broad spectral range, programmable spectral resolution, the small detector fields of view, and an orbiting spacecraft platform will allow CIRS to observe the Saturnian system in the thermal infrared at a level of detail not previously achieved. © 2004 Kluwer Academic Publishers.